Beyond the ‘safe sex’ propaganda - Hadzic, Maja; Khajehei, Marjan (Freund Publishing House Ltd, 2010)
In this paper, we discuss sexual relationships among teenagers, the related issues and suggest addressing the issues through effective education programmes for both teenagers and their parents. We also discuss the main issues resulting from initiation of sexual relationship during adolescence such as unwanted pregnancy, maternal mortality, abortion, sexually transmitted diseases and damaged mental health. In addition, we highlight the lack of adequate sexual education in teenagers and emphasise on the negative influence of TV programmes and the harmful effects of dysfunctional families. Moreover, this article proposes equipping teenagers with knowledge that will help them understand not only physical but also emotional, social, and mental dynamics of sexual relationships. We believe that this approach would intervene much earlier in their life, help teenagers make healthy decision and minimize negative consequences of their personal choices.